PENGARUH PENERAPAN METODE PEMBELAJARAN TALKING STICK TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN FIQIH DI MAN 4 AGAM - Muhammad Raihan; Hamdi Abdul Karim; Wedra Aprison; Charles Charles (ADIBA : JOURNAL OF EDUCATION, 2025)
This research is motivated by the fact that some students have low learning motivation, especially in fiqh subjects because learning only takes place in one direction and the use of less varied learning methods. Learning in class is limited to listening, taking notes, then memorizing the material. This research aims to determine the effect of the Talking Stick Learning Method on Student Learning Motivation in Class 10 Fiqh Subjects on Dhamman and Kafalah Material at MAN 4 Agam. This research was carried out at MAN 4 Agam in May 2024. This research design used a quasi-experimental quantitative method. The population of this study consisted of all class X students. The sample for this research was class X.1 as the experimental class and class X.3 as the control class. The data collection technique uses a questionnaire. The research data was analyzed through a series of quantitative analyses. The research results are as follows: 1) learning motivation increased by 6.71% seen from the results of the students' pre-test and post-test questionnaires. The average student pre-test result was 91.11%, while the student post-test result was 97.28. Motivation which was initially low increased after implementing the Talking Stick learning method. 2) there is a significant influence as shown by the results of the Pairet Simple Test which has a significant value of 0.03 < 0.05. This shows that there is an influence of the Talking Stick learning method on students' learning motivation in fiqh subjects at MAN 4 Agam.